A comparative study on press freedom between Malaysia and Australia / Afiqah Mohammad…[et al.] - Mohammad, Afiqah; Rahim, Nor Aisyah; Abu Yazid, Nurul Azua; Othman, Zaharah (2009)
The press plays vital roles to a well informed society in a democratic country. In Malaysia, the press is restricted from freely carrying out its functions to inform the citizen by a number of laws enacted by Parliament. A number of press laws are said to have restrictive effects on the media. There are a lot of bodies and individuals that have put forward their ideas to have greater freedom of press. These include seeking for a revision on our press laws but such actions are yet to be considered by the authority. This raises a question on to whether the Malaysian press has been given sufficient freedom of press. In carrying out this research, a comparison has been made between the press in Malaysia and Australia. This research is actually an attempt to analyse the constitutional safeguard protecting freedom of press in Malaysia and Australia. Besides, this research will examine the extent of press freedom in Malaysia and Australia. This is a library-based research. Data and information were gathered from the library and internet databases. Findings show that both Malaysia and Australia have certain restrictions on press but to different extent. As compared to Malaysia, in Australia, the press has a self regulatory body which governs matters relating to press. It is hoped that this research can be useful to provide better understanding of knowledge and to provide access for the citizen in area of press freedom due to fact that there are differences of approach between Malaysia and Australia on who draws the balancing rights and restraints.